Effects of imidacloprid-sodium chloride association on survival and reproduction of the stink bug Podisus nigrispinus - Silva-Ramos, Gabryele; De Paulo, Paula Daiana; Toledo, Pedro F. S.; Haddi, Khalid; Cola-Zanuncio, Jose; Oliveira, Eugenio E. (Revista de Ciencias Agrícolas, 2019)
Pesticide effects on natural enemies in an agroecosystem are of paramount importance for integrated pest management programs. Natural enemies can be subject to direct and indirect exposure to insecticides and synergistic molecules (e.g., sodium chloride - NaCl) which are used to control various pests of agricultural crops such as soybean. Here, we evaluated the potential effects of imidacloprid and its interaction with NaCl as an enhancer on the survival and reproductive abilities of the non-target predator Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae). The insects were exposed to the stink bugs control field recommended dose of imidacloprid associated or not with the salt at the concentration of 0.5% (w/v). NaCl as a pesticide enhancer did not affect the survival of P. nigrispinus adults after 48 h of exposure (less than 12% of mortality was always recorded). However, the fifth instar nymph mortality was almost 50%. The effects of imidacloprid on the reproductive parameters of P. nigrispinus included a decrease in the oviposition, showing fewer eggs per day. However, the fertility was not affected. The NaCl addition, therefore, had no effect on the mortality, survival, and reproduction of the non-target predator. The use of NaCl associated to imidacloprid and other pesticides in the presence of P. nigrispinus demonstrated compatibility, however, it requires further evaluation to endorse the set of these pest control strategies.